Coordination of contractual and tort claims in the European law of jurisdiction - Martiny, Dieter (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Under Article 7(1) and Article 7(2) Brussels I-bis Regulation of 2012, there is jurisdiction for contractual and tort claims. The delineation of these matters is not easy, particularly in cases where there is a concurrency of actions. The discussion is continuing even after the Wikingerhof judgment of the European Court of Justice of 24 November 2020. The present article discusses weaknesses associated with different concepts like duties and interests. The introduction of additional elements like the ‘indispensability’ of analysing the contract in cases of tort jurisdiction are difficult to apply and lead to new uncertainty. The admissibility of annex jurisdiction for contract and tort would alleviate the problem.
Keywords: Brussels I-bis Regulation (No. 1215/2012); characterisation; contractual and tort claims; jurisdiction under Article 7(1) and Article 7(2) Brussels I-bis Regulation